EFFECT OF DEBT, FIRM SIZE, AND DIVIDEND POLICY ON FIRM VALUE MEDIATED BY CASH HOLDINGS - Putra, Hasannudin Nursalim; Salim, Ubud; Aisjah, Siti (Jurnal Aplikasi Manajemen, 2023)
The context of this study focuses on the benefits of debt usability, firm size, and dividend policy in increasing the value of cash-mediated companies in LQ45 companies for the period 2017-2020. This study aims to find out and analyze the effect of debt, firm size, and dividend policy on the firm's value, either directly or indirectly, through the mediation of cash holdings. The samples in this study are LQ45-indexed companies from 2017-2020. The samples in this study fall into the purposive sampling category, where respondents are selected based on the criteria specified in this study. The sample numbered 24 companies that can be processed. The analysis method used is descriptive analysis and regression of panel data using the Eviews 10 software application. The results showed that increasing the firm's size will decrease the firm's value while increasing the dividend policy will increase the firm's value. Debt and cash holdings are unable to affect the value of the firm. In addition, only variable debt can negatively affect cash holdings, while the size of the firm and its dividend policy cannot affect cash holdings. This research implies that companies indexed LQ45 need to pay attention to optimal cash holding adequacy because it can be influenced by company debt so that the company can maintain its position in the LQ45 index.